Malnutrition Contributes to Low Lymphocyte Count in Early-Stage Coronavirus Disease-2019 - Zhang, Kai; Qin, Weidong; Zheng, Yue; Pang, Jiaojiao; Zhong, Ning; Fei, Jianchun; Li, Yu; Jian, Xiangdong; Hou, Xinguo; Hu, Zhao; Li, Chen; Wang, Hao; et al. (Frontiers in Nutrition, 2022)
Background & Aims: Lymphocytes play an important role in fighting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections. Low total lymphocyte count (TLC), which contributes to poor clinical outcomes, is common in persons with coronavirus disease 2019 (COVID-19). The current explanation for the cause of low TLC is that it is directly related to the invasiveness of SARS-CoV-2, which attacks lymphocytes. We hypothesized that malnutrition contributes to the development of low TLC in early-stage COVID-19. Methods: We prospectively enrolled 101 patients with confirmed COVID-19. On their first day of hospitalization, we collected baseline and laboratory data, including clinical symptoms; the Sequential Organ Failure Assessment, Nutrition Risk Screening 2002 and Subjective Global Assessment were used to assess patients’ malnutrition status. Multivariable logistic regression was used to identify independent risk factors for low TLC and severe COVID-19. Results: Malnutrition was associated with lower TLC in COVID-19. Fifty-nine (58.4%) patients showed low TLC, 41 (40.6%) were at risk for malnutrition and 18 of them were malnourished. Low TLC was an independent risk factor for severe COVID-19. Compared to patients with normal TLC, those with low TLC more often presented with anorexia, malnutrition, higher SOFA scores (P < 0.05) and comorbidities (diabetes and malignancies). Malnutrition (OR: 3.05, 95% CI: 1.50-6.19, P = 0.006) and SOFA scores (OR: 1.51, 95% CI: 1.04-2.43, P = 0.042) were identified as independent risk factors for low TLC. Conclusions: Malnutrition was common among our patients with early-stage COVID-19, and it contributed to the occurrence of low TLC.